2014
DOI: 10.1002/jso.23646
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous diagnostic platform of genotyping EGFR, KRAS, and ALK in 510 Korean patients with non‐small‐cell lung cancer highlights significantly higher ALK rearrangement rate in advanced stage

Abstract: Simultaneous panel genotyping revealed more prevalent ALK rearrangements than reported in previous studies and their strong association with advanced stage irrespective of sex or smoking history. ALK rearrangement seems to be a marker for aggressive tumor biology and should be assessed in advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 32 publications
7
26
0
Order By: Relevance
“…The incidence of ALK rearrangements was found to be 9.6% (73/763) in NSCLC and 11.0% (54/493) in adenocarcinoma in our study, which was similar to the results previously published in Chinese (Shan et al, 2014;Wang et al, 2014a;Yang et al, 2014) and Asian cohorts (Kim et al, 2014). As previously reported, patients who were ALK-positive were predominantly young women and never/light smokers (Lynch et al, 2004;Rodig et al, 2009;Shaw et al, 2009;Wong et al, 2009;Jokoji et al, 2010;Takahashi et al, 2010;Zhang et al, 2013;Zhang et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The incidence of ALK rearrangements was found to be 9.6% (73/763) in NSCLC and 11.0% (54/493) in adenocarcinoma in our study, which was similar to the results previously published in Chinese (Shan et al, 2014;Wang et al, 2014a;Yang et al, 2014) and Asian cohorts (Kim et al, 2014). As previously reported, patients who were ALK-positive were predominantly young women and never/light smokers (Lynch et al, 2004;Rodig et al, 2009;Shaw et al, 2009;Wong et al, 2009;Jokoji et al, 2010;Takahashi et al, 2010;Zhang et al, 2013;Zhang et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The incidence rate of EGFR mutations in our study was similar to those of other studies evaluating cohorts of Asian ethnicity (Pao et al, 2004;Kim et al, 2014;Wang et al, 2014b). Previous results have indicated that the frequency of EGFR mutation was increased in patients with adenocarcinoma, young women, and never smokers (Lynch et al, 2004;Shaw et al, 2009;Li et al, 2013;Wang et al, 2014b).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Anaplastic lymphoma kinase (ALK)-rearranged non-small cell lung cancer (NSCLC) behaves more aggressively than other NSCLCs, showing early metastasis and an advanced stage at time of diagnosis (1)(2)(3). Similarly, patients with ALK-rearranged NSCLC and high expression of ALK are more likely to be in advanced stages and have worse 2-year progression-free survival rates (4).…”
Section: Introductionmentioning
confidence: 99%